Ragam Qira‘at Mushaf Alquran di Cirebon (Studi atas Mushaf Keraton Kacirebonan) - Abdul Latif; Adib Adib; Mahrus eL-Mawa (UIN Siber Syekh Nurjati Cirebon, 2018)
Islam recognizes the name of qira‘at seven of the seven qira‘at priests who are still practiced and made daily reading only four imams ie. Nafi ', Abu ’Amr, Ibn 'Amir, and ’Asim. Not all of these imams were routinely recited by Muslims. Muslims in Indonesia generally only recognize one qira'at. Hafs from 'Asim. This is at least evident from some of the printed Qur'an that predominantly use the Hafs from 'Asim. From several literatures, there are thousands of religious manuscripts in Indonesia. In Cirebon there are several scientific manuscripts in several palaces residing in Cirebon area. In Kacirebonan palace there are 50 more manuscripts, three of which are ancient Qur'anic manuscripts. Based on the existing reality, this paper will explore the study of the text of the mushaf, especially in his studies of qira‘at. From that background then the question arises. 1. How to write Mushaf Alquran in Kacirebonan palace. 2. How is the variety of qira‘at contained in the mushaf.